Online calibration and compensation of total odometer error in an integrated system. (July 2018) - Li, Leilei; Sun, Hongxing; Yang, Sheng; Ding, Xuewen; Wang, Jin; Jiang, Jinlong; Pu, Xiuhua; Ren, Chunhua; Hu, Ning; Guo, Yongcai
Highlights: Proposed online calibration method of total odometer error. Proposed odometer-aided INS method. Odometer calibration depends on vehicle maneuver. INS/odometer integration can reach 1‰ mileage accuracy after calibration. Abstract: Odometer is a good information source for land vehicle navigation because it can detect the velocity or mileage of a vehicle. Odometer scale factor, misalignment, and level arm with inertial measurement unit are the three sources of integration inaccuracy. However, they are difficult to be calibrated using a single procedure as they vary with many factors, such as the environment temperature, loading, and mounting factors. The online calibration method of the total odometer error and the odometer-aided inertial navigation system algorithm based on Coriolis Law were derived in this study. Vehicle test results indicated that the proposed calibration method can perform a good estimation of total odometer error. Navigation accuracy can be improved significantly with the calibrated odometer when the Global Positioning System declares loss-of-lock, which is approximately 1‰ of the mileage.